MAKNA SIMBOLIK PASAHAT ULOS TUJUNG TU NA MABALU DALAM ADAT BATAK TOBA DI PARBULUAN: KAJIAN SEMIOTIKA CHARLES SANDERS PEIRCE - Manalu, Sanada; Januarsyah Daulay, Muhammad Anggie (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the symbolic meanings contained in the Pasahat Ulos Tujung Tu Na Mabalu tradition of the Batak Toba community through Charles Sanders Peirce’s semiotic perspective. Pasahat Ulos Tujung Tu Na Mabalu is a customary ritual performed for a widow after the death of her husband and contains various cultural signs that reflect social, spiritual, and kinship values. This study aims to describe the icons, indexes, and symbols found in the tradition. The research employed a descriptive qualitative method. Data were collected through observation, interviews, documentation, and literature review. The results show that icons are represented through Ulos Tujung, Ulos Saput, Dekke Na Niarsik, and water in the manuapi ritual, which resemble the conditions and experiences of mourning. Indexes are reflected in the customary actions that indicate emotional recovery, social status changes, and the transition of na mabalu after losing a spouse. Symbols are manifested in Ulos Tujung, Boras Sipir Ni Tondi, Dekke Na Niarsik, umpasa, and ritual procedures that signify respect, solidarity, customary protection, and hopes for a better life. Thus, the signs contained in the Pasahat Ulos Tujung Tu Na Mabalu tradition function as a medium for conveying cultural values and strengthening social relations within the Batak Toba community.